Reply to Hastings, et al., and Meshnick. - Pyae Phyo, A; Ashley, E; Anderson, T; Carrara, V; Woodrow, C; White, N; Nosten, F (Oxford University Press, 2016)
A response to the comments of Professor Meshnik and Dr Hastings on the paper "Phyo, A.P., et al., Declining Efficacy of Artemisinin Combination Therapy Against P. Falciparum Malaria on the Thai–Myanmar Border (2003–2013): The Role of Parasite Genetic Factors. Clinical Infectious Diseases, 2016."